When social hierarchy matters grammatically: Investigation of the processing of honorifics in Korean - Kwon, Nayoung; Sturt, Patrick (Cognition, 2024)
Korean grammar encodes relative social hierarchies among interlocutors in various ways. This study utilized honorific subject-verb agreement in Korean to investigate how social hierarchies are processed during sentence comprehension. The experimental results showed that honorific violations elicited processing difficulties. The use of an honorific verb with an unhonorifiable subject resulted in lower naturalness ratings, longer reading times, and elicited a P600, similar to effects observed with number, person, and gender agreement in Spanish or English. These findings suggest that social hierarchies have become integrated into grammar, constraining how native Korean speakers process sentences. However, the agreement between honorific subjects and verbs seems asymmetrical; the mismatch effect was smaller or absent when an honorifiable subject was not accompanied by an honorific verb, suggesting that while an honorific verb requires an honorifiable subject, the reverse is not necessarily true. The results indicate that the -si agreement in Korean is a form of morpho-syntactic agreement, despite its asymmetrical nature.